Споредба на магнетотерапија наспроти терапија со интерферентни струи кај пациенти со оперативно решена пертрохантерна фрактура на фемурот тип Kyle I, II - Митревска, Билјана (Медицински факултет, УКИМ, Скопје, 2016)
Introduction: The increase in the average life span has made treatment of upper femoral fractures a major problem of modern surgery. Non-surgical treatment methods do not offer satisfactory anatomical and functional results. Surgical treatment, dynamic implants is the method of choice in pertrohanteric fixation of fractures. Objectives: To compare the effects of two physical modalities, magnetic therapy versus treatment with interferential currents in the physical treatment and rehabilitation of patients with surgically determined pertrohanteric femoral fracture with DHS-type KYLE I, II and indicate the reasons for any differences . Material and Methods: The study represents a prospective randomized clinical trial implemented at the Institute for Physical Medicine and Rehabilitation - Skopje. Include two groups with 90 participants with surgical pertochanteric femoral fracture, Kyle types I, II with dynamic fixation implant-DHS (Dynamic hip screw). Respondents are divided into two groups: Examined group - 45 patients is treated with kinesitherapy and Magnetic therapy and control group - which has 45 patients treated with kinesitherapy and interferential currents. Respondents were followed for one year, during which were performed three examinations, the first control on the day of discharge, 6 and 12 months, from the first review which is input for selected patients who meet the criteria for inclusion in research. Results: Patients treated with kinesiotherapy and interferential currents have 7.1% less likely after 12 months to move without aid, compared with patients in the experimental group (Kynesitherapy and Magnetic therapy). On physical examination after 6 and 12 months, the analysis indicated that the flexion with straight knee and abduction of the hip, in the experimental group was significantly higher compared to the control group. After 12 months flexion with bent knee and hip extension of the experimental group was significantly greater than in the control group. For 12 months after knee flexion and extension in the experimental group was significant in the control group. Upon physical examination of admission, discharge, 6 and 12 months. The analysis did not indicate statistically significant difference between the two groups in terms of adduction, internal and external rotation of the hip, dorsal and plantar flexion of the ankle. After the analysis, patients in the experimental group have 4,125 times more likely, after 12 months have shaped callus compared to control group. Upon physical examination after discharge, 6 and 12 months, Harrist hip score in the experimental group was significantly higher, ie the patients were significantly improved compared to the control group. In the experimental group after 12 months pointed to two independent predictors (age, personality) due to 73.8% from changes in Harris score, the only age, due to 58.7%. In the observation group, 12 months after the analysis pointed to three independent predictors (gender and age) due to 49.5%, of which only the age, due to 36.4% after 12 months .Analizata indicated that patients in the experimental group have better quality of life comparied with patients in the control group with respect to all 8 parameters of SF-36. Statistically significant difference charter has the following parameters: physical functioning, pain and general health, in addition to the experimental group. Conclusions: In the postoperative rehabilitation of pertrochanteric femoral fractures, Kyle type I, II with fixation dynamic implant-DHS, therapy of choice is magnetic therapy and kinesitherapy, from which improvement in functional status as well as in the stimulation of osteogenesis and quality of life in elderly patients.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Анастасика Попоска.
Keywords: pertrochanteric femoral fracture, DHS-dynamic hip screw, magnetic therapy, interferential currents, kynesitherapy